Family environment, parental stressors, and post-traumatic stress disorder in the parents of premature infants in the Neonatal Intensive Care Unit - Mahdieh Arabzadeh; Batool Tirgari; Jamileh Farokhzadian; Sakineh Mohammadalizadeh (Hygeia Press di Corridori Marinella, 2022)
Background: The birth of premature infants and their admission to the Neonatal Intensive Care Unit (NICU) causes emotional stress in parents and in the whole family. This event can affect the interaction between family members and disrupt the family's environment. Therefore, the aim of the present study was to estimate the family environment, the parental stressors and the level of post-traumatic stress disorder (PTSD) in the parents of premature infants admitted to NICU.  Methods: This descriptive-analytic study was conducted in the two NICUs of a Specialized and Educational Hospital in South-East of Iran. A total of 140 parents (70 mothers and 70 fathers) were enrolled in the study using convenience sampling method. The data collection tool included a demographic questionnaire of parents and neonates, a Family Environment Scale (FES), a Parental Stressor Scale (PSS), and the Impact of Event Scale - Revised (IES-R). Data analysis was carried out using descriptive and inferential statistics, including independent t-test, one-way ANOVA, and Pearson correlation co-efficient in SPSS® ver. 18.  Results: The family environment was evaluated at the moderate level by mothers and fathers in the FES, with mean scores of 97.48 ± 11.46 and 98.70 ± 10.50, respectively. The mean score of parental stressors in the PSS was moderate in mothers (2.90 ± 0.86) and low in fathers (2.55 ± 0.90). Also, the mean PTSD score in the IES-R was moderate in fathers (35.10 ± 18.79) and in mothers (43.01 ± 17.14). The results showed no significant relationship between family environment and PTSD in mothers (r = 0.11, p = 0.36) and fathers (r = 0.04, p = 0.75), but a significant relationship was found for both parents in terms of parental stressors and PTSD (mothers: r = 0.48, p = 0.0001; fathers: r = 0.59, p = 0.0001).  Conclusion: The results revealed that family environment scores and PTSD scores in parents of premature infants were at the moderate level. The parents who experienced stressors without adequate support were at risk for PTSD. In this regard, parents should be considered as patients by the healthcare team who, recognizing signs of parental stress early, could play an important role in preventing adverse effects of stress on parents themselves and on the infants. Educational and counseling interventions by NICU nurses can help parents to adapt to NICU environment and to use coping strategies to manage stress, promote family cohesion, and reduce the risk of PTSD.